Lithium secondary battery

By introducing a prelithiation process into the silicon-based negative electrode of lithium secondary batteries and limiting the use range of silicon discharge capacity, the problem of difficulty in achieving high capacity and fast charging when using silicon-based negative electrodes in lithium secondary batteries is solved, while improving the Battery life performance.

CN119365992APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049406.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-15
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When using silicon-based negative electrodes, existing lithium secondary batteries are difficult to achieve high capacity and fast charging, and their life performance is deteriorated due to volume expansion.

Method used

By introducing pre -lithium chemical processes in the lithium secondary battery, the scope of the use of silicon discharge capacity is limited to ensure that the total discharge capacity is below 35%, the upper end of the silicon discharge capacity is below 57%, the lower end is above 13%or more Essence

Benefits of technology

It achieves a battery with high capacity and high energy density, while solving the problem of life performance degradation caused by volume expansion and ensuring the life performance of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365992A_ABST
    Figure CN119365992A_ABST
Patent Text Reader

Abstract

The present application relates to a lithium secondary battery comprising: a silicon-based negative electrode; a positive electrode; a diaphragm; and an electrolyte, in which the positive electrode or the silicon-based negative electrode is a pre-lithiated electrode, in which the silicon-based negative electrode has a silicon discharge capacity use range of 35% or less of the total negative electrode discharge capacity, and in which the silicon discharge capacity of the silicon-based negative electrode has an upper end of 57% or less and a lower end of 13% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0183766 filed in the Korean Intellectual Property Office on December 23, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a lithium secondary battery. Background Art

[0003] As the use of fossil fuels has increased rapidly, there is an increasing demand for the use of alternative or clean energy, and as part of this trend, the most active area of ​​research is in the field of power generation and storage using electrochemical reactions.

[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to be gradually expanded.

[0005] With the technological development and increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, methods for manufacturing high-density electrodes with higher energy density per unit volume have been actively studied.

[0006] Typically, a secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator. The negative electrode comprises a negative electrode active material for inserting and extracting lithium ions from the positive electrode. As a negative electrode material, carbon-based materials such as graphite have excellent stability and reversibility, but have limitations in terms of capacity. Therefore, in the field of high capacity, attempts to use Si-based materials with high theoretical capacity as negative electrode materials are increasing.

[0007] That is, lithium secondary batteries are usually manufactured by using lithium intercalation compounds such as LiCoO2 or LiMn2O4 for the positive electrode and non-lithium intercalation materials such as carbon or Si materials for the negative electrode. During charging, the lithium ions embedded in the positive electrode move to the negative electrode through the electrolyte. During discharge, the lithium ions move back to the positive electrode from the negative electrode. During charging, the lithium moving from the positive electrode to the negative electrode reacts with the electrolyte, thereby forming a passivation film, i.e., a solid electrolyte interface (SEI), on the surface of the negative electrode. SEI inhibits the movement of electrons required for the reaction of the negative electrode with the electrolyte, thereby preventing the decomposition of the electrolyte, thereby stabilizing the structure of the negative electrode. On the other hand, the formation of SEI is irreversible, resulting in the consumption of lithium ions. That is, the lithium consumed due to the formation of SEI will not return to the positive electrode during the subsequent discharge process, resulting in a decrease in the capacity of the battery.

[0008] On the other hand, in order to improve the performance of lithium secondary batteries, it is necessary to develop technologies to accelerate the charging rate. In order to quickly charge lithium secondary batteries, the movement rate of lithium ions must be fast during the process of lithium ion embedding into the negative electrode. Therefore, battery design is being carried out to reduce the diffusion distance of lithium by forming a negative electrode active material layer with a thickness of a film level, and to increase conductivity by forming a carbon coating layer on the surface of the negative electrode active material layer, thereby reducing internal resistance, thereby achieving high output.

[0009] However, it is difficult to achieve high capacity using a negative electrode having such a thin film negative electrode active material layer. In addition, it is difficult to achieve fast charging in a negative electrode with high capacity. In addition, when a silicon-based negative electrode is used, the content of Si in the negative electrode is increased in order to increase the energy density, and therefore, the volume expands rapidly during the charging process, disconnecting the conductive path, resulting in degradation of the battery characteristics, and therefore, the capacity decreases from the initial stage. In addition, for a silicon-based negative electrode, when the charge and discharge cycle is repeated, lithium ions are not uniformly charged in the depth direction of the negative electrode, and the reaction proceeds on the surface, accelerating the degradation of the surface, and therefore, performance needs to be improved in terms of battery cycles.

[0010] Therefore, in order to solve the problems that arise when a silicon-based compound having excellent fast charging performance is used alone as a negative electrode active material, various methods have been discussed, such as a method of controlling the driving potential, a method of additionally coating a thin film on the active material layer, a method of suppressing the volume expansion itself, such as a method of controlling the particle size of the silicon-based compound, or developing an adhesive that can suppress the volume expansion of the silicon-based compound to prevent the conductive path from being disconnected.

[0011] However, since the above method may deteriorate the performance of the battery, there are limitations in application, so that there are still limitations in the commercialization of negative electrode batteries with a high content of silicon-based compounds that have excellent fast charging performance. As the ratio of the silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, so that the silicon-based active material on the surface side is destroyed, and due to the occurrence of uneven pre-lithiation, problems arise in improving life characteristics.

[0012] Therefore, there is a need to study a lithium secondary battery having improved cycle performance while using a negative electrode including a silicon-based active material for high capacity.

[0013] Prior art documents

[0014] (Patent Document 1) Japanese Patent Publication No. 2009-080971 Summary of the invention

[0015] [Technical issues]

[0016] As a result of research on the above-mentioned problem, it has been confirmed through research that when a silicon-based negative electrode (especially a pure Si negative electrode) is used as the negative electrode to ensure the capacity characteristics, the use area of ​​the silicon-based negative electrode can be limited by adjusting the NP ratio and introducing a pre-lithiation process, thereby ensuring the life characteristics.

[0017] Therefore, the present application relates to a lithium secondary battery including a silicon-based negative electrode.

[0018] [Technical solution]

[0019] An exemplary embodiment of the present specification provides a lithium secondary battery, comprising a silicon-based negative electrode; a positive electrode; a separator; and an electrolyte, wherein the positive electrode or the silicon-based negative electrode is a pre-lithiation electrode, wherein the silicon discharge capacity of the silicon-based negative electrode has a usage range of less than 35% of the total negative electrode discharge capacity, and wherein the upper end (upper end) of the silicon discharge capacity of the silicon-based negative electrode is less than 57% and the lower end (lower end) thereof is greater than 13%.

[0020] [Beneficial Effects]

[0021] The main feature of the lithium secondary battery according to the present application is that a pre-lithiation process is applied to the silicon-based negative electrode or positive electrode, and when the silicon-based negative electrode is used, the total discharge capacity usage range is limited, specifically, the upper and lower ends of the discharge capacity are controlled.

[0022] As a result, it is possible to manufacture batteries that can achieve high capacity and high energy density, which are the advantages of using a silicon-based negative electrode, while solving the existing problem of deterioration in life performance due to volume expansion during repeated cycles.

[0023] That is, the main feature of the lithium secondary battery according to the present application is that the life performance of the lithium secondary battery is ensured by limiting the use area of ​​silicon included in the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A lithium secondary battery according to the present application is shown.

[0025] <Description of Reference Numerals>

[0026] 10: Negative electrode collector layer

[0027] 20: Negative electrode active material layer

[0028] 30: Diaphragm

[0029] 40: Positive electrode active material layer

[0030] 50: Positive electrode collector layer

[0031] 100: Negative electrode

[0032] 200: Positive DETAILED DESCRIPTION

[0033] Before describing the present invention, some terms are first defined.

[0034] In the present specification, unless otherwise specifically described, when a part “includes,” “contains,” or “has” a constituent element, this does not mean to exclude other constituent elements but means that other constituent elements may further be included.

[0035] In this specification, “p to q” means a range of “p or more and q or less”.

[0036] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) by using BELSORP-mini II available from BEL Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.

[0037] In this specification, "Dn" means particle size distribution, and means the particle size at n% point in the cumulative distribution of the number of particles according to the particle size. That is, D50 is the particle size at 50% point in the cumulative distribution of the number of particles according to the particle size, D90 is the particle size at 90% point in the cumulative distribution of the number of particles according to the particle size, and D10 is the particle size at 10% point in the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured by using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac S3500), wherein when the laser beam passes through the particle, the diffraction pattern is measured with the change of particle size, and then the particle size distribution is calculated.

[0038] In the present specification, the description "a polymer contains a specific monomer as a monomer unit" means that the monomer participates in a polymerization reaction and is contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, this is interpreted as the same as the polymer containing the monomer as a monomer unit.

[0039] In the present specification, it should be understood that the term "polymer" is used in a broad sense including copolymers unless otherwise explicitly referred to as "homopolymer".

[0040] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-converted molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.

[0041] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0042] An exemplary embodiment of the present specification provides a lithium secondary battery, comprising a silicon-based negative electrode; a positive electrode; a separator; and an electrolyte, wherein the positive electrode or the silicon-based negative electrode is a pre-lithiation electrode, wherein the silicon discharge capacity of the silicon-based negative electrode has a usage range of less than 35% of the total negative electrode discharge capacity, and wherein the upper end of the silicon discharge capacity of the silicon-based negative electrode is less than 57% and the lower end is more than 13%.

[0043] The present application can manufacture a battery that can achieve high capacity and high energy density (which is the advantage of using a silicon-based negative electrode), while being able to solve the existing problem of deterioration of life performance due to volume expansion during repeated cycles. That is, the main feature of the lithium secondary battery according to the present application is that the life performance of the lithium secondary battery is ensured by limiting the use area of ​​the silicon contained in the negative electrode.

[0044] Figure 1 The stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application is shown. Specifically, it can be seen that the negative electrode 100 includes a negative electrode active material layer 20 on one surface of the negative electrode collector layer 10, and it can be seen that the positive electrode 200 includes a positive electrode active material layer 40 on one surface of the positive electrode collector layer 50, and the negative electrode 100 for lithium secondary batteries and the positive electrode 200 for lithium secondary batteries are formed into a stacking structure with a separator 30 interposed therebetween.

[0045] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the silicon discharge capacity of the silicon-based negative electrode has a usage range of less than 35% of the total negative electrode discharge capacity, and wherein the upper end of the silicon discharge capacity of the silicon-based negative electrode is less than 57% and the lower end is more than 13%.

[0046] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein an NP ratio of the lithium secondary battery is 170% or more and 280% or less.

[0047] In an exemplary embodiment of the present application, the NP ratio may satisfy the following Formula A.

[0048] [Formula A]

[0049] N / P ratio=discharge capacity per unit area of ​​negative electrode / discharge capacity per unit area of ​​positive electrode.

[0050] In the present invention, "discharge capacity per unit area" refers to the discharge capacity per unit area in the first cycle of the negative electrode or the positive electrode.

[0051] The discharge capacity per unit area of ​​the negative electrode can be obtained by the following method. Specifically, a half-cell is manufactured using a negative electrode sample containing a negative electrode active material and a counter electrode (e.g., a lithium metal electrode) facing the negative electrode sample. The discharge capacity measured by charging and discharging the half-cell is divided by the weight of the negative electrode active material to obtain the "discharge capacity of the negative electrode sample per unit weight of the negative electrode active material". A secondary battery is manufactured using a negative electrode containing the same negative electrode active material as the negative electrode active material used in the half-cell and a positive electrode containing the same positive electrode active material. The "discharge capacity of the negative electrode sample per unit weight of the negative electrode active material" is multiplied by the weight of the negative electrode active material contained in the secondary battery, and then divided by the area of ​​the negative electrode contained in the secondary battery to obtain the discharge capacity per unit area of ​​the negative electrode.

[0052] The discharge capacity per unit area of ​​the positive electrode can be obtained by the following method. Specifically, a half-cell is manufactured using a positive electrode sample containing a positive electrode active material and a counter electrode (e.g., a lithium metal electrode) facing the positive electrode sample. The discharge capacity measured by charging and discharging the half-cell is divided by the weight of the positive electrode active material to obtain the "positive electrode sample discharge capacity per unit weight of positive electrode active material". A secondary battery is manufactured using a positive electrode containing the same positive electrode active material as the positive electrode active material used in the half-cell and a negative electrode containing the same negative electrode active material. The "positive electrode sample discharge capacity per unit weight of positive electrode active material" is multiplied by the weight of the positive electrode active material contained in the secondary battery, and then divided by the area of ​​the positive electrode contained in the secondary battery to obtain the discharge capacity per unit area of ​​the positive electrode.

[0053] The lithium secondary battery according to the present application has a feature of limiting the USOC of the negative electrode by introducing a pre-lithiation process for the positive electrode or the negative electrode and adjusting the NP ratio and applying it.

[0054] In the present application, the upper and lower ends of the discharge capacity refer to the upper and lower end values ​​based on the active Li discharged in the total load of the negative electrode calculated based on the % value of USOC, and can be values ​​calculated from the load and initial efficiency of the positive electrode and the initial efficiency of the negative electrode.

[0055] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the upper end of the silicon discharge capacity of the silicon-based negative electrode is greater than 45% and less than 57%, and the lower end of the silicon discharge capacity of the silicon-based negative electrode is greater than 13% and less than 28%.

[0056] In another exemplary embodiment, the upper end of the silicon discharge capacity of the silicon-based negative electrode may be 45% or more and 57% or less, preferably 46% or more and 53% or less, and more preferably 48% or more and 52% or less.

[0057] In another exemplary embodiment, the lower end of the silicon discharge capacity of the silicon-based negative electrode may satisfy 13% to 28%, preferably 14% to 25%, more preferably 16% to 24.5%.

[0058] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the difference between the upper and lower ends of the silicon discharge capacity is less than 35%.

[0059] That is, the difference between the upper and lower ends of the silicon discharge capacity may be expressed as ΔSi, which may refer to the capacity portion used in the silicon-based negative electrode.

[0060] In another exemplary embodiment, the difference between the upper and lower ends of the silicon discharge capacity may be less than 35%, preferably 34.8% or less, more preferably 34.5% or less, and may satisfy 20% or more, preferably 25% or more.

[0061] That is, the use range of the negative electrode can be adjusted according to the N / P ratio and pre-lithiation as described above, thereby ensuring the life characteristics while maintaining the characteristics of the silicon-based negative electrode.

[0062] In an exemplary embodiment of the present application, the silicon-based negative electrode or positive electrode may be a pre-lithiated electrode. Pre-lithiation means replenishing the electrode with lithium in advance, and all methods used in the art such as transfer process, electrochemical process and SLMP process may be applied.

[0063] The positive electrode, the negative electrode, the electrolyte, and the separator included in the lithium secondary battery will be described below, respectively.

[0064] According to the present application, the silicon-based negative electrode may include a negative electrode current collector layer and a negative electrode active material layer disposed on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer contains a negative electrode active material layer composition.

[0065] The thickness of the negative electrode current collector layer is generally 1 μm to 100 μm. There is no particular limitation on such a negative electrode current collector as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum cadmium alloy, etc. can be used. In addition, the negative electrode current collector layer may have fine irregularities formed on the surface to enhance the bonding force of the negative electrode active material, and can be used in various forms, such as a film, sheet, foil, net, porous body, foam body or non-woven fabric body.

[0066] However, the thickness can be variously modified according to the type and use of the negative electrode used, and is not limited thereto.

[0067] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material.

[0068] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include one or more selected from the group consisting of a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0069] In an exemplary embodiment of the present application, the negative electrode active material layer may include a negative electrode active material layer composition, and the negative electrode active material layer composition may include a silicon-based active material, a negative electrode conductive material, and a negative electrode binder.

[0070] In an exemplary embodiment of the application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloy.

[0071] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, may include 70 parts by weight or more of SiO x (x = 0).

[0072] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, SiO xThe content of (x=0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.

[0073] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on 100 parts by weight of the silicon-based active material as described above, the above range contains pure Si particles (SiO2) not combined with other particles or elements. x (x=0)).

[0074] It is noted that the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. If the average particle size is less than 5 μm, the specific surface area of ​​the particles is excessively increased, causing the viscosity of the negative electrode slurry to increase excessively. Therefore, the particles constituting the negative electrode slurry cannot be dispersed smoothly. In addition, if the size of the silicon-based active material is too small, the composite composed of a conductive material and a binder in the negative electrode slurry reduces the contact area between the silicon particles and the conductive material, increasing the possibility of disconnection of the conductive network, thereby reducing the capacity retention rate. On the other hand, if the average particle size is greater than 10 μm, there are too large silicon particles, making the surface of the negative electrode not smooth, causing uneven current density during charge and discharge. In addition, if the silicon particles are too large, the phase stability of the negative electrode slurry becomes unstable, deteriorating the processability. As a result, the capacity retention rate of the battery is reduced.

[0075] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).

[0076] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a silicon-containing film or coating.

[0077] In an exemplary embodiment of the present application, the content of the negative electrode active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0078] In an exemplary embodiment of the present application, the content of the silicon-based active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0079] In another exemplary embodiment, based on 100 parts by weight of the negative electrode active material layer composition, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.

[0080] The negative electrode active material layer composition according to the present application uses a specific negative electrode conductive material and a negative electrode binder that can control the volume expansion rate during charge and discharge even when a significantly high capacity silicon-based active material is used within the above range. Therefore, even when the silicon-based active material is within the above range, the negative electrode active material layer composition does not reduce the performance of the negative electrode and has excellent output characteristics during charge and discharge.

[0081] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and its sphericity (roundness) is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0082] In the present application, sphericity (roundness) is determined by the following formula 1, where A is the area and P is the boundary line.

[0083] [Formula 1]

[0084] 4πA / P 2

[0085] In the art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, due to the increasing demand for high-capacity batteries, attempts to mix and use silicon-based compounds have increased in order to increase capacity. However, the silicon-based compounds are limited in that their volume expands rapidly during charge and discharge, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby reducing the performance of the battery.

[0086] Therefore, in an exemplary embodiment of the present application, the negative electrode active material layer composition may include a negative electrode conductive material and a negative electrode binder. That is, during charge and discharge, the negative electrode conductive material plays a role in ensuring a conductive path, and the binder plays a role in retaining the negative electrode conductive material.

[0087] In an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of a point-shaped conductive material, a planar conductive material, and a linear conductive material.

[0088] In an exemplary embodiment of the present application, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, form conductivity without causing chemical changes, and has a round or dot shape. Specifically, the dot-shaped conductive material can be one or more substances selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of high conductivity and excellent dispersibility.

[0089] In an exemplary embodiment of the present application, the BET specific surface area of ​​the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g and above 60 m 2 / g or less.

[0090] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 40 nm to 60 nm.

[0091] In an exemplary embodiment of the present application, the conductive material may include a planar conductive material.

[0092] The planar conductive material refers to a conductive material that improves conductivity by increasing the surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion. The planar conductive material can be expressed as a plate-like conductive material or a block-like conductive material.

[0093] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0094] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size leads to easy dispersion without excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.

[0095] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm to 1.5 μm, a D50 of 4.0 μm to 5.0 μm, and a D90 of 7.0 μm to 15.0 μm.

[0096] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area having a high BET specific surface area or a planar conductive material with a low specific surface area may be used.

[0097] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation. However, in particular, the planar conductive material according to the present application can affect the electrode performance to a certain extent due to the dispersion effect, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0098] In an exemplary embodiment of the present application, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g or above.

[0099] In another exemplary embodiment, the BET specific surface area of ​​the planar conductive material may be 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m2 / g or less.

[0100] In another embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area can meet 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 250 m 2 / g or less.

[0101] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.

[0102] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or entangled in a bundle or rope-like shape in an orientation that makes the longitudinal axes of the carbon nanotube units substantially the same. The carbon nanotube unit comprises a graphite sheet having a cylindrical shape with a nanometer diameter and an sp2 bonding structure. In this case, the characteristics of a conductor or a semiconductor may be exhibited according to the rolling angle and structure of the graphite sheet. Compared with entangled carbon nanotubes, the bundle-type carbon nanotubes may be dispersed more evenly during the manufacture of the negative electrode, and may form a conductive network more smoothly in the negative electrode, thereby improving the conductivity of the negative electrode.

[0103] In an exemplary embodiment of the present application, the negative electrode conductive material may include a linear conductive material, and the linear conductive material may be a carbon nanotube.

[0104] In an exemplary embodiment of the present application, the carbon nanotube may be SWCNT or / and MWCNT. When the linear conductive material is SWCNT, the length of the SWCNT may be 0.5 μm to 100 μm, preferably 1 μm to 80 μm.

[0105] In an exemplary embodiment of the present application, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode active material layer composition.

[0106] In another exemplary embodiment, the content of the negative electrode conductive material may be 5 parts by weight or more and 40 parts by weight or less, preferably 5 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the negative electrode active material layer composition.

[0107] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material and a linear conductive material, and a ratio of the planar conductive material to the linear conductive material may satisfy 1:0.001 to 1:0.3.

[0108] In an exemplary embodiment of the present application, since the negative electrode conductive material comprises the planar conductive material and the linear conductive material and respectively satisfies the above-mentioned composition and ratio, the life characteristics of the existing lithium secondary battery are not significantly affected, wherein the number of sites at which the battery can be charged and discharged is increased, resulting in excellent output characteristics at a high C rate.

[0109] The negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active materials that cause the electrode volume to expand greatly due to charge and discharge, while the positive electrode conductive material is used to impart a certain conductivity and at the same time act as a buffer during rolling, and is completely different from the negative electrode conductive material of the present invention in terms of structure and function.

[0110] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material only has smaller particles than the active material, the conductive material has the characteristics of improving the output characteristics and imparting a certain conductivity, and is completely different from the negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of structure and function.

[0111] In an exemplary embodiment of the present application, the structure and function of the plate-shaped conductive material used as the above-mentioned negative electrode conductive material are different from the structure and function of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape and used to promote the storage and release of lithium ions.

[0112] On the other hand, the plate-like conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be expressed as plate-like graphite. That is, the plate-like conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material for securing a conductive path in a planar shape inside the negative electrode active material layer rather than playing a role in storing and releasing lithium.

[0113] That is, in the present application, using plate-like graphite as a conductive material means that graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than a material that functions to store or release lithium. In this case, the negative electrode active material contained together has high capacity characteristics in terms of storing and releasing lithium, and is used to store and release all lithium ions transferred from the positive electrode.

[0114] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.

[0115] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.

[0116] The negative electrode binder according to an exemplary embodiment of the present application is used to retain the silicon-based active material and the negative electrode conductive material to prevent distortion and structural deformation of the negative electrode structure when the volume of the silicon-based active material expands and relaxes. When such a role is met, all conventional negative electrode binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.

[0117] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more, 8 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition.

[0118] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, the use of the aqueous binder in the above-mentioned weight portion enables the use of a dot-shaped conductive material with a low functional group content. In addition, the above-mentioned characteristics make the dot-shaped conductive material hydrophobic and make the bonding strength between the conductive material / binder excellent.

[0119] In an exemplary embodiment of the present application, the silicon-based negative electrode may be formed by coating a negative electrode slurry including the negative electrode active material layer composition on one surface or both surfaces of the negative electrode current collector layer.

[0120] In an exemplary embodiment of the present application, the negative electrode slurry may include a negative electrode active material layer composition and a slurry solvent.

[0121] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy a range of 5% or more and 40% or less.

[0122] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.

[0123] The solid content of the negative electrode slurry may mean the content of the negative electrode composition included in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0124] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, so that particle aggregation of the negative electrode composition is minimized, thereby effectively forming the negative electrode active material layer.

[0125] In an exemplary embodiment of the present application, the slurry solvent may be used without limitation as long as it can disperse the negative electrode composition, and specifically, water or NMP may be used.

[0126] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.

[0127] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0128] The porosity varies depending on the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, the above-mentioned range is satisfied, so that the conductivity and resistance of the electrode are within an appropriate range.

[0129] In an exemplary embodiment of the present application, the positive electrode includes a positive electrode collector layer and a positive electrode active material layer provided on one surface or both surfaces of the positive electrode collector layer, and the positive electrode active material layer contains a positive electrode active material layer composition.

[0130] In an exemplary embodiment of the present application, the positive electrode active material layer may include a positive electrode active material layer composition, and the positive electrode active material layer composition may include one or more selected from the group consisting of a positive electrode active material, a positive electrode conductive material, and a positive electrode binder.

[0131] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel each surface-treated with carbon, nickel, titanium, silver, etc., etc. can be used. In addition, the thickness of the positive electrode collector layer can generally be 1 to 500 μm, and the surface of the positive collector layer can be formed with fine concave-convex to enhance the adhesion with the positive active material. For example, the positive electrode collector can be used in different forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0132] In an exemplary embodiment of the present application, a lithium secondary battery is provided, wherein the thickness of each of the positive electrode collector layer and the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of each of the positive electrode active material layer and the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0133] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may include a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe yOne or more of the group consisting of PO4 (M: transition metal, x+y=1). In this case, the positive electrode active material is not limited thereto.

[0134] Specifically, as the positive electrode active material, commonly used NCM or NCMA may be used.

[0135] Typically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; 1-c2 M c2 Ni-site lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which part of Li in the chemical formula is replaced by alkaline earth metal ions, etc., but is not limited thereto. The positive electrode may be Li metal.

[0136] In an exemplary embodiment of the present application, the positive electrode active material includes a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), and the lithium composite transition metal compound includes single particles or secondary particles, and the average particle size (D50) of the single particles can be greater than 1 μm.

[0137] For example, the average particle size (D50) of the single particles may be 1 μm to 12 μm, 1 μm to 8 μm, 1 μm to 6 μm, greater than 1 μm to 12 μm, greater than 1 μm to 8 μm, or greater than 1 μm to 6 μm.

[0138] Even when single particles with a small average particle size (D50) of 1 μm or more and 12 μm or less are formed, the particle strength can be excellent. 2When the rolling is carried out at a force of 650 kgf / cm, the particle strength of the single particle can be 100 MPa to 300 MPa. 2 When the single particle is rolled with a strong force, the phenomenon of increasing fine particles in the electrode due to particle breakage is also alleviated, which improves the life characteristics of the battery.

[0139] The single particle may be produced by mixing a transition metal precursor with a lithium source material and firing. The secondary particle may be produced by a method different from that of the single particle, and its composition may be the same as or different from that of the single particle.

[0140] The method of forming the single particles is not particularly limited, but may generally be formed by overfiring at an elevated firing temperature, or may be produced by using an additive that facilitates overfiring such as a grain growth promoter, or by changing a starting material.

[0141] For example, the firing is carried out at a temperature at which a single particle can be formed. For this reason, the firing should be carried out at a temperature higher than the temperature during the manufacture of the secondary particles. For example, when the composition of the precursor is the same, the firing should be carried out at a temperature about 30°C to 100°C higher than the temperature during the manufacture of the secondary particles. The firing temperature for forming the single particle can vary according to the metal composition in the precursor. For example, when a single particle is formed using a high Ni NCM-based lithium composite transition metal oxide having a nickel (Ni) content of 80 mol % or more, the firing temperature can be about 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive electrode active material containing a single particle with excellent electrochemical performance can be manufactured. If the firing temperature is lower than 790°C, a positive electrode active material containing a lithium composite transition metal compound in the form of a secondary particle can be manufactured. If the firing temperature exceeds 950°C, over-burning occurs, and the layered crystal structure is not properly formed, so that the electrochemical performance may be deteriorated.

[0142] In this specification, the single particle is a term used to distinguish from typical secondary particles obtained by aggregation of tens to hundreds of primary particles, and is a concept including a single particle composed of one primary particle and a quasi-single particle form which is an aggregate of 30 or less primary particles.

[0143] Specifically, in the present invention, the single particle may be a single particle consisting of one primary particle, or a quasi-single particle form that is an aggregate of 30 or less primary particles, and the secondary particle may be an aggregate of hundreds of primary particles.

[0144] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.

[0145] In the present invention, the single particle may be a single particle consisting of one primary particle, or a quasi-single particle form that is an aggregate of 30 or less primary particles, and the secondary particle may be an aggregate of hundreds of primary particles.

[0146] The lithium composite transition metal compound may further include secondary particles. The secondary particles refer to a form formed by the aggregation of primary particles, which can be separated from the concept of single particles (including one primary particle, a single particle, and a quasi-single particle form which is an aggregation of 30 or less primary particles).

[0147] The particle size (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles may be 0.05 m 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g.

[0148] In another exemplary embodiment of the present application, the secondary particles are aggregates of primary particles, and the average particle size (D50) of the primary particles is 0.5 μm to 3 μm. Specifically, the secondary particles may be aggregates of hundreds of primary particles, and the average particle size (D50) of the primary particles may be 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0149] When the average particle size (D50) of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of aggregates of the primary particles forming the lithium nickel oxide particles increases, and the inhibitory effect on particle breakage during rolling is reduced. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles may become longer, thereby increasing resistance and reducing output characteristics.

[0150] According to another exemplary embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles. As a result, even if the single particles are formed to have a small particle size, they can have excellent particle strength, and therefore, the phenomenon of increasing particles in the electrode due to particle rupture is alleviated, which can improve the life characteristics of the battery.

[0151] In an exemplary embodiment of the present application, an average particle diameter (D50) of the single particles is 1 μm to 18 μm smaller than an average particle diameter (D50) of the secondary particles.

[0152] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.

[0153] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above-mentioned range is met, even if the single particles are formed to have a small particle size, they can have excellent particle strength. As a result, the phenomenon of increased microparticles in the electrode due to particle breakage is alleviated, which improves the life characteristics and energy density of the battery.

[0154] According to another exemplary embodiment of the present application, based on 100 parts by weight of the positive electrode active material, the content of the single particle is 15 parts by weight to 100 parts by weight. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 20 parts by weight to 100 parts by weight or 30 parts by weight to 100 parts by weight.

[0155] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.

[0156] When the single particles contained are within the above range, the combination with the above negative electrode material can show excellent battery characteristics. In particular, when the content of the single particles is 15 parts by weight or more, the phenomenon of increasing fine particles in the electrode due to particle rupture in the rolling process after the electrode is made can be alleviated, which can improve the life characteristics of the battery.

[0157] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the content of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the content of the secondary particles may be 0 parts by weight or more.

[0158] When the above range is met, the above effect caused by the presence of the single particle in the positive electrode active material can be maximized. In the case of a positive electrode active material containing the secondary particles, its composition may be the same as or different from the composition exemplified in the above single particle positive electrode active material, and may refer to an aggregated form of a single particle.

[0159] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be greater than 80 parts by weight and less than 99.9 parts by weight, preferably greater than 90 parts by weight and less than 99.9 parts by weight, more preferably greater than 95 parts by weight and less than 99.9 parts by weight, and most preferably greater than 98 parts by weight and less than 99.9 parts by weight.

[0160] In addition to the positive electrode active material, the positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder.

[0161] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples may include graphite, such as natural graphite and artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, etc., and any one thereof or a mixture of two or more thereof may be used.

[0162] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.

[0163] The separator is used to separate the negative electrode from the positive electrode and provide a migration path for lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is commonly used in secondary batteries, in particular, it is preferred to use a separator with high moisture retention capacity for electrolytes and low resistance to electrolyte ion migration. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure having more than two layers thereof. In addition, a typical porous nonwoven fabric can be used, such as a nonwoven fabric formed of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be selectively used.

[0164] In the present application, examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte that can be used to manufacture the lithium secondary battery, but are not limited thereto.

[0165] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0166] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.

[0167] Especially, in the carbonate system organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents, and because their dielectric constant is high, thus dissociate lithium salts well, therefore can preferably use them.When the cyclic carbonate and the straight chain carbonate of low viscosity and low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio and used, the electrolyte with high conductivity can be prepared, so such combination can be more preferred.

[0168] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in the non-aqueous electrolyte. For example, as anions of the lithium salt, one or more substances selected from the group consisting of: F - , Cl - ,I - 、NO3 - 、N(CN) 2- 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .

[0169] In order to improve the life characteristics of the battery, inhibit the decline of the battery capacity, improve the discharge capacity of the battery, etc., the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0170] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0171] Invented Pattern

[0172] Hereinafter, preferred embodiments will be provided in order to better understand the present invention. It is obvious to those skilled in the art that the embodiments are provided only to illustrate the present invention, and various changes and variants are possible within the scope and technical spirit of the present invention. It is also natural that such changes and variants fall within the scope of the claims enclosed herein.

[0173] <Production Example>

[0174] (1) Manufacturing of negative electrode

[0175] <Manufacturing of Negative Electrode Active Material Layer>

[0176] A negative electrode active material layer composition was prepared using Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. A negative electrode slurry (solid concentration: 28 wt %) was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry.

[0177] The first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0178] As a mixing method, the first conductive material, the second conductive material, the binder, and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the active material was added thereto, and the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.

[0179] The negative electrode slurry was prepared at 3.00 mg / cm 2A loading amount of 200 Å was coated on both surfaces of a copper current collector (thickness: 15 μm) serving as a negative electrode current collector, which was then rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 23 μm).

[0180] (2) Manufacturing of positive electrode

[0181] The positive electrode slurry (solid concentration: 78 wt %) was prepared by the following steps: LiNi 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Temeco) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry at a weight ratio of 97:1.5:1.5.

[0182] The positive electrode slurry was prepared at 537 mg / 25 cm 2 The positive electrode was prepared by coating the positive electrode with a loading amount of 77 μm on both surfaces of an aluminum current collector (thickness: 12 μm) used as a positive electrode current collector, which was then rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm).

[0183] The lithium secondary batteries shown in the following Table 1 were manufactured by interposing a polyethylene separator between the positive electrode and the negative electrode and injecting an electrolyte.

[0184]

[0185] In Table 1 above, the preparation method of the electrode using pre-lithiation is as follows.

[0186] <Pre-lithiation using transfer method>

[0187] A transfer stack was manufactured by depositing lithium metal on the upper portion of PET coated with a release layer (the release layer was coated on one surface of the PET; I-One film, with a thickness of 20 μm to 50 μm) using a PVD method so that the thickness (pre-lithiation amount) was as shown in Table 1 above, and pre-lithiation was performed by transferring the lithium metal layer to the upper portion of the electrode shown in Table 1.

[0188] Experimental Example 1: Evaluation of Life Performance

[0189] For the lithium secondary battery containing the negative electrode prepared in the embodiment and the comparative example, the life and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary battery was subjected to a 4.2-3.2 V, 1 C / 0.5 C cycle test, and the number of cycles when the capacity retention rate reached 80% was measured and shown in Table 2 below.

[0190] Capacity retention rate (%) = {(discharge capacity in the Nth cycle) / (discharge capacity in the first cycle)}×100

[0191] Experimental Example 2: Measurement and Evaluation of Resistance Increase Rate

[0192] After the secondary battery was charged and discharged at 0.33 C / 0.33 C (4.2-3.0 V) during the test of Experimental Example 1 and the capacity retention rate was measured every 50 cycles, the secondary battery was discharged at SOC50 with a 2.5 C pulse to measure the resistance, and then the resistance increase rate was compared and analyzed.

[0193] In order to evaluate the resistance increase rate measurement, data of 600 cycles were each calculated, and the results are shown in Table 2 below.

[0194]

[0195] As can be seen from Tables 1 and 2 above, it can be confirmed that in the case of the lithium secondary battery according to the embodiment, when the silicon-based negative electrode is used and the positive electrode or the negative electrode is pre-lithiated by a specific amount, the total discharge capacity usage range is limited, specifically, the upper and lower ends of the discharge capacity are controlled.

[0196] From this, it was confirmed that it is possible to manufacture batteries that can achieve high capacity and high energy density (which are the advantages of using a silicon-based negative electrode) while solving the existing problems of deterioration in life performance and increased resistance due to volume expansion during repeated cycles.

[0197] That is, the main feature of the lithium secondary battery according to the present application is that the life performance of the lithium secondary battery is ensured by limiting the use area of ​​silicon included in the negative electrode.

[0198] In Comparative Example 1 in which pre-lithiation was not applied to the positive electrode or the negative electrode, the NP ratio range was also low, and both the upper and lower ends were deeply used, so it was confirmed that the life performance degradation of lithium caused by charge and discharge was worse and the resistance increase rate was high.

[0199] In the case of Comparative Examples 2 and 3, pre-lithiation was performed, but the degree of pre-lithiation did not satisfy the upper and lower capacities of the present invention. Specifically, Comparative Example 2 is equivalent to a case where the upper range of the negative electrode capacity exceeds the range according to the present application, and Comparative Example 3 is equivalent to a case where the lower range of the negative electrode capacity is lower than the range according to the present application. In these cases, it can be confirmed that the performance is not as reduced as in Comparative Example 1, but compared with Examples 1 to 3, the life performance is reduced due to the volume expansion of the negative electrode.

Claims

1. A lithium secondary battery comprising: Silicon-based negative electrode; positive electrode; Diaphragms; and Electrolytes, wherein the positive electrode or the silicon-based negative electrode is a pre-lithiation electrode, The silicon discharge capacity of the silicon-based negative electrode is used in a range of less than 35% of the total negative electrode discharge capacity, and The upper end of the silicon discharge capacity of the silicon-based negative electrode is 57% or less and the lower end is 13% or more. 2 . The lithium secondary battery according to claim 1 , wherein a NP ratio of the lithium secondary battery is 170% or more and 280% or less. 3 . The lithium secondary battery according to claim 1 , wherein the difference between the upper and lower ends of the silicon discharge capacity is less than 35%.

4. The lithium secondary battery according to claim 1, wherein the upper end of the silicon discharge capacity of the silicon-based negative electrode is 45% or more and 57% or less, and The lower end of the silicon discharge capacity of the silicon-based negative electrode is greater than or equal to 13% and less than or equal to 28%.

5. The lithium secondary battery according to claim 1, wherein the silicon-based negative electrode comprises a negative electrode current collector layer and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising a negative electrode active material layer composition, The positive electrode comprises a positive electrode current collector layer and a positive electrode active material layer disposed on one surface or both surfaces of the positive electrode current collector layer, wherein the positive electrode active material layer comprises a positive electrode active material layer composition, wherein the negative electrode active material layer composition comprises a silicon-based active material, a negative electrode conductive material and a negative electrode binder, and Wherein the silicon-based active material includes one or more selected from the group consisting of SiO x (x = 0), SiO x (0 < x < 2), and metal impurities, and based on 100 parts by weight of the silicon-based active material, includes 70 parts by weight or more of SiO x (x = 0). 6 . The lithium secondary battery according to claim 5 , wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

7. The lithium secondary battery according to claim 5, wherein the positive electrode active material layer composition comprises a positive electrode active material, and The positive electrode active material comprises a material selected from the group consisting of LiNi x Co y Mn z O2 (x+y+z=1), LiNi a Co b Mn c Al d O2(a+b+c+d=1)、LiMn2O4、LiNi 0.5 Mn 1.5 O2 and LiM x Fe y One or more selected from the group consisting of PO4 (M: transition metal, x+y=1).

8. The lithium secondary battery according to claim 5, wherein the thickness of the positive electrode current collector layer and the thickness of the negative electrode current collector layer are respectively 1 μm or more and 100 μm or less, and The thickness of the positive electrode active material layer and the thickness of the negative electrode active material layer are respectively 20 μm or more and 500 μm or less.